One piece : baroque works, 22-23-24 - Oda, Eiichirō, 1975-; Caselman, Lance (Shonen Jump manga., 2014)
"As a child, Monkey D. Luffy dreamed of becoming King of the Pirates. But his life changed when he accidentally ate the Gum-Gum Fruit, an enchanted Devil Fruit that gave him the ability to stretch like rubber. Its only drawback? He'll never be able to swim again--a serious handicap for an aspiring sea dog! Years later, Luffy sets off on his quest to find the "One Piece," said to be the greatest treasure in the world ... Luffy's epic clash with Baroque Works pirate captain Crocodile continues, while deposed princess Vivi and the rest of the Straw Hat crew race against time to save the ancient kingdom of Alabasta. Just when it seems smooth sailing is ahead, Luffy and crew discover an interloper among their ranks! Who is this former Baroque Works member, and what does she want from the Straw Hats?"--Page 4 of cover